(untitled) (Research, Society and Development, 2023)
The present work aims to describe the main methodologies that contribute to the prevention and treatment of gonarthrosis. The present study is a narrative review of the literature, which aims to examine and synthesize the available literature on treatments used in knee osteoarthritis – gonarthrosis. Until a few decades ago, the treatment of osteoarthritis, also known as gonarthrosis when it affects the knees, was limited to approaches such as the use of simple analgesics, anti-inflammatories, physical measures such as weight loss, muscle strengthening and physiotherapy, in addition to corticosteroid injections. In the most serious cases, the only option was surgical treatment. Several non-pharmacological therapies are used to treat knee osteoarthritis. Among them, the following stand out: acupuncture, manual therapy, physiotherapy, devices (orthotics, shoes, walkers), weight loss, electrotherapy (TENS, ultrasound and laser) and thermal modalities such as cryotherapy, thermotherapy and hydrotherapy. In conclusion, knee osteoarthritis (KOA) is a complex condition that involves degeneration of articular cartilage, changes in the bones, muscles and ligaments that stabilize the knee joint. Conservative treatment plays a fundamental role in the management of KOA, aiming to alleviate pain and improve the patient’s function and quality of life.